PT. Haleyora Power Bandung’s Employee Work Productivity - Cornelia, Sapta; Hapsari, Ayuningtyas Yuli (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Employees at the company have a responsibility in carrying out all company actions that have duties related to all company activities. PT. Haleyora Power Bandung has implemented an occupational safety and health (K3) program to minimize work accidents that may occur to employees who work directly in the field as well as good communication between the company and employees. But the problem that occurs is the level of work productivity of employees at PT. Haleyora Power Bandung can be said to be low because the target given by the company is not achieved. This study aims to determine how occupational safety and health (K3), communication, and work productivity of employees at PT. Haleyora Power Bandung and to find out how occupational safety and health (K3) and communication influence employee productivity at PT. Haleyora Power Bandung, either partially or simultaneously. The research method used is descriptive and verification methods. The sample used in this study were all employees of PT. Haleyora Power Bandung. Data processing is done by using multiple linear regression, analysis of the coefficient of determination, and testing hypotheses. Based on the results of the study, it can be said that there is an influence between occupational safety and health (K3) at PT. Haleyora Power Bandung and the influence of communication on employee productivity at PT. Haleyora Power Bandung as well as occupational safety and health (K3) and communication simultaneously affect the work productivity of employees at PT. Haleyora Power Bandung.